Strategi Media Relations PT Prima Praxis Komunika dalam Menghasilkan Publikasi di Media Massa - Sumartias, Suwandi; Diandra, Mikha Puan; Setianti, Yanti (Jurnal Pewarta Indonesia, 2024)
The trend of using fixed broadband internet has resulted in increasing competition among internet business sector providers. Link Net as one of the affected companies conducted several communication strategies to surpass competitors in gaining market share levels. To ensure the success of this strategy, Link Net worked closely with Praxis in implementing a media relations strategy to generate positive news publications. However, Link Net's highest level of publication in the mass media is in fact not directly proportional to the level of market share among competitors. The purpose of this research is to find out the media relations strategy used by Praxis to generate positive news publications for Link Net amid competitors along with its objectives and implementation process. The research used a case study method with a qualitative approach. Research data were obtained through interviews, observations, and literature studies. The results showed that Praxis' media relations strategy is divided into three, namely media event, relationship management, and relationship development. These three strategies are carried out to achieve three specific objectives, which is to convey public information, obtain high credibility marketing, and resolve crises. The implementation of Praxis' media relations strategy is carried out through research, preparation, implementation, and evaluation. Overall, Praxis' media relations strategy has been carried out ideally. However, there is still room for development for Praxis to implement strategies more creatively, maximize value, and complete technical aspects, such as standardizing SOPs and division of labor for each team member, so that the resulting publications can have a significant influence on Link Net's market share level.